The Nuclear Receptor—Co-repressor Complex in Control of Liver Metabolism and Disease - Liang, Ning; Jakobsson, Tomas; Fan, Rongrong; Treuter, Eckardt (Frontiers in Endocrinology, 2019)
Hepatocytes are the major cell-type in the liver responsible for the coordination of metabolism in response to multiple signaling inputs. Coordination occurs primarily at the level of gene expression via transcriptional networks composed of transcription factors, in particular nuclear receptors (NRs), and associated coregulators, including chromatin-modifying complexes. Disturbance of these networks by genetic, environmental or nutritional factors can lead to metabolic dysregulation and has been linked to the progression of non-alcoholic fatty liver disease (NAFLD) towards steatohepatitis and even liver cancer. Since there are currently no approved therapies, major efforts are dedicated to identify the critical factors that can be employed for drug development. Amongst the identified factors with clinical significance are currently lipid-sensing NRs including PPARs, LXRs and FXR. However, major obstacles of NR-targeting are the undesired side effects associated with the genome-wide NR activities in multiple cell-types. Thus, of particular interest are coregulators that determine NR activities, context-selectivity, and associated chromatin states. Current research on the role of coregulators in hepatocytes is still premature due to the large number of candidates, the limited number of available mouse models, and the technical challenges in studying their chromatin occupancy. As a result, how NR-coregulator networks in hepatocytes are coordinated by extracellular signals, and how NR-pathway selectivity is achieved, remains currently poorly understood. We will here review a notable exception, namely a fundamental transcriptional corepressor complex that during the past decade has become the probably most-studied and best-understood physiological relevant coregulator in hepatocytes. This multiprotein complex contains the core subunits HDAC3, NCOR, SMRT, TBL1, TBLR1 and GPS2 and is referred to as the ‘NR-corepressor complex’. We will particularly discuss recent advances in characterizing hepatocyte-specific loss-of-function mouse models and in applying genome-wide sequencing approaches including ChIP-seq. Both have been instrumental to uncover the role of each of the subunits under physiological conditions and in disease models, but they also revealed insights into the NR target range and genomic mechanisms of action of the corepressor complex.